The Influence of Leadership and Supervision on Employee Performance in Baitul Maal wat Tamwil (BMT) Surya Madani Ngemplak Branch Boyolali Regency - Budiwinarto, Kim (Jurnal Ekuisci, 2023)
The purpose of this study is to find out the influence of leadership on employee performance, and the influenceof insight on employee performance at BMT Surya Madani Ngemplak Branch, Boyolali Regency. The method used in this study is quantitative method. The sample inthis study was employees at BMT Surya Madani Branch Ngemplak Kabupatent Boyolali as many as 30 respondents. The data analysis techniques used are multiple linear regression analysis, t test, F test, and coefficient of determination. The results showed that leadership and supervision had a significant effect on the performance of employees at BMT Surya Madani Ngemplak Branch of Boyolali Regency, both partially and simultaneously. The amount of influence of leadership and supervision has a significant effect on employee performance at BMT Surya Madani Ngemplak Branch, Boyolali Regency is 86.4%.